A microengineered model of RBC transfusion-induced pulmonary vascular injury - Jeongyun Seo (Nature Portfolio, 2017)
Abstract Red blood cell (RBC) transfusion poses significant risks to critically ill patients by increasing their susceptibility to acute respiratory distress syndrome. While the underlying mechanisms of this life-threatening syndrome remain elusive, studies suggest that RBC-induced microvascular injury in the distal lung plays a central role in the development of lung injury following blood transfusion. Here we present a novel microengineering strategy to model and investigate this key disease process. Specifically, we created a microdevice for culturing primary human lung endothelial cells under physiological flow conditions to recapitulate the morphology and hemodynamic environment of the pulmonary microvascular endothelium in vivo. Perfusion of the microengineered vessel with human RBCs resulted in abnormal cytoskeletal rearrangement and release of intracellular molecules associated with regulated necrotic cell death, replicating the characteristics of acute endothelial injury in transfused lungs in vivo. Our data also revealed the significant effect of hemodynamic shear stress on RBC-induced microvascular injury. Furthermore, we integrated the microfluidic endothelium with a computer-controlled mechanical stretching system to show that breathing-induced physiological deformation of the pulmonary microvasculature may exacerbate vascular injury during RBC transfusion. Our biomimetic microsystem provides an enabling platform to mechanistically study transfusion-associated pulmonary vascular complications in susceptible patient populations.